Single‐cell transcriptomics reveals a senescence‐associated IL‐6/CCR6 axis driving radiodermatitis. Issue 8 (4th July 2022) - Paldor, Mor; Levkovitch‐Siany, Orr; Eidelshtein, Dana; Adar, Revital; Enk, Claes D; Marmary, Yitzhak; Elgavish, Sharona; Nevo, Yuval; Benyamini, Hadar; Plaschkes, Inbar; Klein, Shiri; Mali, Alex; et al.
Abstract: Irradiation‐induced alopecia and dermatitis (IRIAD) are two of the most visually recognized complications of radiotherapy, of which the molecular and cellular basis remains largely unclear. By combining scRNA‐seq analysis of whole skin‐derived irradiated cells with genetic ablation and molecular inhibition studies, we show that senescence‐associated IL‐6 and IL‐1 signaling, together with IL‐17 upregulation and CCR6 + ‐mediated immune cell migration, are crucial drivers of IRIAD. Bioinformatics analysis colocalized irradiation‐induced IL‐6 signaling with senescence pathway upregulation largely within epidermal hair follicles, basal keratinocytes, and dermal fibroblasts. Loss of cytokine signaling by genetic ablation in IL‐6 −/− or IL‐1R −/− mice, or by molecular blockade, strongly ameliorated IRIAD, as did deficiency of CCL20/CCR6‐mediated immune cell migration in CCR6 −/− mice. Moreover, IL‐6 deficiency strongly reduced IL‐17, IL‐22, CCL20, and CCR6 upregulation, whereas CCR6 deficiency reciprocally diminished IL‐6, IL‐17, CCL3, and MHC upregulation, suggesting that proximity‐dependent cellular cross talk promotes IRIAD. Therapeutically, topical application of Janus kinase blockers or inhibition of T‐cell activation by cyclosporine effectively reduced IRIAD, suggesting the potential of targeted approaches for the treatment of dermal side effects in radiotherapy patients. Synopsis: Irradiation‐induced alopecia and dermatitis (IRIAD) represent two of the most prominent side effects of radiotherapy in the skin. This study utilized scRNA‐seq analysis to identify driving factors of IRIAD in order to facilitate development of targeted therapeutic approaches for its prevention. IRIAD in mice is strongly associated with upregulation of senescence pathways involving IL‐6 and IL‐1 signaling, together with IL‐17 signaling. Loss of IL‐6 and IL‐1 signaling, or of CCL20/CCR6‐mediated immune cell migration strongly ameliorated IRIAD, while simultaneously reducing irradiation‐induced cellular senescence. IL‐6‐deficiency strongly reduced IL‐17, CCL20, and CCR6 upregulation, while loss of CCR6‐mediated immune cell migration reciprocally diminished IL‐6 and IL‐17 upregulation, and loss of immune privilege. IRIAD is effectively ameliorated by treatment with Janus kinases blockers or cyclosporine A. Abstract : Irradiation‐induced alopecia and dermatitis (IRIAD) represent two of the most prominent side effects of radiotherapy in the skin. In this study, Paldor et al applied scRNA‐seq analysis to identify driving factors of IRIAD in order to facilitate the development of targeted therapeutic approaches for its prevention.